Pharmacological potential of methylxanthines: Retrospective analysis and future expectations. Issue 16 (8th September 2019) - Monteiro, João; Alves, Marco G.; Oliveira, Pedro F.; Silva, Branca M.
ABSTRACT: Methylated xanthines (methylxanthines) are available from a significant number of different botanical species. They are ordinarily included in daily diet, in many extremely common beverages and foods. Caffeine, theophylline and theobromine are the main methylxanthines available from natural sources. The supposedly relatively low toxicity of methylxanthines, combined with the many beneficial effects that have been attributed to these compounds through time, generated a justified attention and a very prolific ground for dedicated scientific reports. Methylxanthines have been widely used as therapeutical tools, in an intriguing range of medicinal scopes. In fact, methylxanthines have been/were medically used as Central Nervous System stimulants, bronchodilators, coronary dilators, diuretics and anti-cancer adjuvant treatments. Other than these applications, methylxanthines have also been hinted to hold other beneficial health effects, namely regarding neurodegenerative diseases, cardioprotection, diabetes and fertility. However, it seems now consensual that toxicity concerns related to methylxanthine consumption and/or therapeutic use should not be dismissed. Taking all the knowledge and expectations on the potential of methylxanthines into account, we propose a systematic look at the past and future of methylxanthine pharmacologic applications, discussing all the promise and anticipating possible constraints. Anyways, methylxanthines will still substantiate considerable meaningful research and discussion for years to come.